The Relationship of Parenting Patterns to Student Achievement in Elementary School - Amalia Mustafa; M Yunus Sudirman (Universitas Muhammadiyah Enrekang, 2022)
Abstract: This study aims to determine the parenting applied by the parents of students, student achievement, the relationship between parenting parents with student achievement. The research was conducted at SDN 45 Talaga, Enrekang District, Enrekang Regency. This type of research is ex post facto using a quantitative approach. The research population was 183 students of SDN 45 Talaga. The number of samples is 33 students with a non-probability sampling technique, namely purposive sampling. Data collection was done by observation, documentation and questionnaires. Data analysis was carried out by observation, documentation and questionnaires. Descriptive data analysis, prerequisite test and hypothesis submission with the help of SPSS version 20.0 for windows. The results of this study indicate that there are 3 types of parenting, namely: democratic parenting, permissive parenting, authoritarian parenting. Learning achievement is in 4 categories, namely less, low, medium, and high. Parenting style has a significant relationship with student achievement at SDN 45 Talaga. Abstrak: Penelitian ini bertujuan untuk mengetahui pola asuh yang diterapkan oleh orang tua siswa, prestasi belajar siswa, hubungan antara pola asuh orangtua dengan prestasi belajar siswa. Penelitian dilaksanakan di SDN 45 Talaga Kecamatan Enrekang Kabupaten Enrekang. Jenis penelitian adalah ex post facto dengan menggunakan pendekatan kuantitatif. Populasi penelitian adalah siswa SDN 45 Talaga sebanyak 183 siswa. Jumlah sampel 33 siswa dengan teknik non probability sampling yaitu purposive sampling. Pengambilan data dilakukan dengan observasi, dokumentasi dan angket. Analisis data dilakukan dengan observasi, dokumentasi dan angket. Analisis data secara deskriptif, uji prasyarat dan pengajuan hipotesis dengan bantuan program SPSS versi 20,0 for windows. Hasil penelitian ini menunjukkan ada 3 jenis pola asuh yaitu : pola asuh demokratis, pola asuh permisif, pola asuh otoriter. Prestasi belajar berada pada 4 kategori, yaitu kurang, rendah, sedang, dan tinggi. Pola asuh orang tua memiliki hubungan yang signifikan dengan prestasi belajar siswa SDN 45 Talaga.